Calibration of CVD-diamond based dosimeter in high-power electron and X-ray radiation fields - Kutny, V.E.; Nikiforov, V.I.; Opalev, O.A.; Rogov, Yu.V.; Rybka, A.V.; Shevchenko, V.A.; Shlyakhov, I.N.; Strelnitsky, V.E.; Tenishev, A.Eh.; Uvarov, V.L. (Вопросы атомной науки и техники, 2014)
Results of a study of dosimetry characteristics of a prototype of the detector based on a polycrystalline diamond film (CVD-diamond) produced in NSC KIPT are summarized. The techniques of the detector calibration against the electron and X-ray radiation dose rate are developed. The conditions of calibration were studied by means of computer simulation. For determination of detector sensitivity to electron radiation, it was placed inside of a standard polystyrene phantom. An additional filter of electrons was used at measurement in the X-ray field. Every time detector irradiation was carried out together with the Harwell Red Perpex 4034 dosimeters, which registrations provided the calibration data. The measurements, executed at the LU-10, EPOS and LU-40 linacs of NSC KIPT, have demonstrated, that the values of detector sensitivity against each type of radiation are close and conform to ones obtained earlier for the low-intensity radiation fields. Considering significant radiation durability of the CVD-diamond, it enables its application in technological dosimetry.